1996
DOI: 10.1021/es960249+
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Eh and H2 Measurements for Delineating Redox Processes in a Contaminated Aquifer

Abstract: Measurements of oxidation−reduction potential (E h) and concentrations of dissolved hydrogen (H2) were made in a shallow groundwater system contaminated with solvents and jet fuel to delineate the zonation of redox processes. E h measurements ranged from +69 to −158 mV in a cross section of the contaminated plume and accurately delineated oxic from anoxic groundwater. Plotting measured E h and pH values on an equilibrium stability diagram indicated that Fe(III) reduction was the predominant redox process in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(99 citation statements)
references
References 10 publications
(12 reference statements)
5
92
0
Order By: Relevance
“…Different approaches have been used to assess the redox conditions during transformation of TCE such as the concentration of either the parent compound or electron donor or of reduced species such as Fe 2+ , HS -and CH 4 (Damgaard et al, 2013;Hunkeler et al, 2011). As described above, H 2 concentrations can also be used as an indicator of the dominant TEAP in natural or contaminated groundwater systems (Chapelle et al, 1996;Lovley and Goodwin, 1988). From our previous study using different synthetic Fe minerals, it has been shown that the competition between TCE reduction and Fe reduction is influenced by Fe mineralogy (Paul et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Different approaches have been used to assess the redox conditions during transformation of TCE such as the concentration of either the parent compound or electron donor or of reduced species such as Fe 2+ , HS -and CH 4 (Damgaard et al, 2013;Hunkeler et al, 2011). As described above, H 2 concentrations can also be used as an indicator of the dominant TEAP in natural or contaminated groundwater systems (Chapelle et al, 1996;Lovley and Goodwin, 1988). From our previous study using different synthetic Fe minerals, it has been shown that the competition between TCE reduction and Fe reduction is influenced by Fe mineralogy (Paul et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Competing microbial populations include denitrifiers, methanogens, acetogens, sulfate-reducers and iron-reducers. Iron and sulfate are the most important alternative electron acceptors due to their ubiquity in aquifer systems and the similarity of the H 2 threshold for their respective TEAPs: ~2 nM for dechlorination [111], 0.1-0.8 nM for iron reduction [56], 1-4 nM for sulfate reduction [17,57].…”
Section: Introductionmentioning
confidence: 99%
“…Though amorphous iron has been shown to inhibit sulfate reduction and methanogenesis (Lovley & Phillips 1987), significant increases in spatial and temporal Fe(II) concentrations are measured in aquifers where other TEAPs that are less energetically favorable (sulfate reduction, methanogenesis) are active and considered to be the dominant TEAP due to higher H 2 concentrations Chapelle et al 1995;Chapelle et al 1996;Chapelle et al 1997). One possible reason for less energetically favorable TEAPs occurring in iron reducing zones is that, due to the less bioavailable fraction present in aquifer sediments, the bioavailability of Fe(III) limits competitive exclusion of H 2 concentrations.…”
Section: Resultsmentioning
confidence: 99%